Study guides

☆☆

Q: Factor 3x squared plus 6xy plus 3y squared?

Write your answer...

Submit

Still have questions?

Related questions

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)

3x(2y + 1)

3x2+6xy+3y2= 3(x2+2xy+y2)= 3(x+y)2

(3x - y)(3x - y)

9x2 - 6xy + y2 - 81 = (3x - y)2 - 92 = (3x - y - 9)(3x - y + 9)

2y(3x + 1)

-3x(2y - 1)

3x

9x^2-6xy+y^2 = (y-3x)^2 (y-3x)^2-81 -> ((y-3x)+9)((y-3x)-9)

It is: 3x*(x+7)

(3x + 1)(x + 5)

(x + 5)(3x + 1)

3(x2 + 3x + 1)

(3x + 3y)(x + y) or 3(x + y)2

(3x - y+ 2)(3x + y + 2)

If that's -18y2, the answer is (3x - 2y)(x + 9y)

3x(2x + 1)

(3x - 2)(x + 8)

(6x + t)(3x + t)

(3x - y)(3x - y) - 81

6xyz(3x + 2y + z)

(3x - 1)(x + 2)

(x - 1)(3x + 5)

It is: x(x+3)

3x2 + x = x*(3x + 1)